2020
DOI: 10.18326/ijims.v10i1.49-77
|View full text |Cite
|
Sign up to set email alerts
|

Islamism and Nationalism among Niqabis Women in Egypt and Indonesia

Abstract: The phenomenon of the increasing number of niqabis in Indonesia and Egypt has become  concern to the government, academics and also civil society. This is due to the involvement of the niqabis or women with the niqab in terrorist networks. Those piece of cloth covering the face is not merely the manifestation of faith but apparently entails a certain ideological doctrine of the so-called Islam kaffah (ultimate Islam) through the establishemnt of Islamic khilafah (Islamic caliphate) as opposed to democracy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 2 publications
0
15
1
2
Order By: Relevance
“…Besides, unlike Tarik Kulenovi's study that sees the niqab as a form of resistance to the mainstream of modernity (Kulenović, 2006), this study provides evidence and arguments that the niqab-wearing is a form of resistance to local values, traditional religious practices, non-sharia-based clothing, and market domination by investors. Thus, this study differs from previous findings that the niqab is an ideological doctrine that deals with democratic systems and nationalism (Dzuhayatin, 2020); identity politics (Pirol & Aswan, 2021); political identity (Saputra, Tanjung, & Augus, 2021); the niqab policy damages human rights and group welfare (Syed, 2021); and the ban on the niqab is a form of social injustice (Cohen-Almagor, 2021).…”
Section: A Introductioncontrasting
confidence: 94%
See 2 more Smart Citations
“…Besides, unlike Tarik Kulenovi's study that sees the niqab as a form of resistance to the mainstream of modernity (Kulenović, 2006), this study provides evidence and arguments that the niqab-wearing is a form of resistance to local values, traditional religious practices, non-sharia-based clothing, and market domination by investors. Thus, this study differs from previous findings that the niqab is an ideological doctrine that deals with democratic systems and nationalism (Dzuhayatin, 2020); identity politics (Pirol & Aswan, 2021); political identity (Saputra, Tanjung, & Augus, 2021); the niqab policy damages human rights and group welfare (Syed, 2021); and the ban on the niqab is a form of social injustice (Cohen-Almagor, 2021).…”
Section: A Introductioncontrasting
confidence: 94%
“…That is, more than 50% of women who wear the niqab support the khilafah system. According to him, one of four niqabis considers that the system implemented by the Indonesian government now is taghut (non-Islamic) (Dzuhayatin, 2020). Moreover, 15% agree to defend Islam by using violence (Dzuhayatin, 2020).…”
Section: Resistance To Tradition and Secularismmentioning
confidence: 99%
See 1 more Smart Citation
“…Memakai cadar merupakan salah satu pilihan berpakaian bagi kaum perempuan di dunia ini berdasarkan atas keyakinan yang kuat (Dzuhayatin, 2020). Memakai cadar bagi perempuan merupakan sebuah cara untuk menunjukkan eksistensi diri dalam kehidupan.…”
Section: Pendahuluanunclassified
“…Another study investigating Islamism and nationalism. It was shown that Islamism threats nationalism which more than 50% of Indonesian niqabis support the Caliphate system, and nearly 15% agree to defend Islam by means of violence (Dzuhayatin, 2020).…”
Section: Introductionmentioning
confidence: 99%